2016
DOI: 10.1063/1.4966209
|View full text |Cite
|
Sign up to set email alerts
|

Carrier density and lifetime for different dopants in single-crystal and polycrystalline CdTe

Abstract: CdTe defect chemistry is adjusted by annealing samples with excess Cd or Te vapor with and without extrinsic dopants. We observe that Group I (Cu and Na) elements can increase hole density above 1016 cm−3, but compromise lifetime and stability. By post-deposition incorporation of a Group V dopant (P) in a Cd-rich ambient, lifetimes of 30 ns with 1016 cm−3 hole density are achieved in single-crystal and polycrystalline CdTe without CdCl2 or Cu. Furthermore, phosphorus doping appears to be thermally stable. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The V Cd intrinsic defect forms an acceptor, and electron paramagnetic resonance estimates a transition energy within 0.47 eV above the valence band maximum 18 , 19 . Measured levels of intrinsically-formed acceptor concentration are often <10 16 cm −3 in single crystal material 20 which is substantially lower than expected from stoichiometric deviation, and higher levels are often not stable 21 . The problem is that while the desired V Cd defect formation is favored, compensating antisite defects such as Te Cd are also favored, leading to the neutral defect V Cd -Te Cd .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The V Cd intrinsic defect forms an acceptor, and electron paramagnetic resonance estimates a transition energy within 0.47 eV above the valence band maximum 18 , 19 . Measured levels of intrinsically-formed acceptor concentration are often <10 16 cm −3 in single crystal material 20 which is substantially lower than expected from stoichiometric deviation, and higher levels are often not stable 21 . The problem is that while the desired V Cd defect formation is favored, compensating antisite defects such as Te Cd are also favored, leading to the neutral defect V Cd -Te Cd .…”
Section: Resultsmentioning
confidence: 80%
“…In CdTe photovoltaics, a Group V doping approach on the anion site has received little attention until recently. Substitutional defects using P, As, and Sb on Te lattice sites form shallow acceptors with estimated transition energies for (0/-) of 0.07 eV, 0.10 eV, and 0.23 eV above the valence band maximum 21 , 25 , as listed in Table 1 . In this scenario, the challenge is ensuring that both sufficient V Te sites exist and that dopant substitution dominates over interstitial occupancy.…”
Section: Resultsmentioning
confidence: 99%
“…This can reduce harmful Te on Cd (Te Cd ) antisites that may limit lifetime, improve stability, and increase hole density compared to traditional Cu and Te-rich chemistries [9]. Continuing to build fundamental understanding is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Group I dopants tend to self-compensate, and while they can be incorporated at low temperatures due to fast diffusion, the fast diffusion also creates stability issues and self-compensation that can limit hole density [1][2][3][4][5]. Furthermore, these elements form somewhat deep acceptors [6], 100-200 meV above the valance band, which can reduce lifetime [7,8] in addition to the lifetime reducing mid-gap states associated with Te-rich stoichiometry. In CdTe solar technology, the use of Cl and Cu as dopants or passivants has failed to produce hole density greater than 10 15 cm -3 and contributed to the stagnation of open-circuit voltage (V OC ) for 30 years [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent results have indicated that CdTe with Group V dopants placed substitutionally on the Te lattice sites can achieve radiatively limited lifetimes and hole concentrations exceeding 10 17 cm -3 [13]. Early data also suggest that Group V dopants appear to remain more stable [8]; however, incorporating these elements is more difficult.…”
Section: Introductionmentioning
confidence: 99%